MODERN CHALLENGES AND DEVELOPMENT SCENARIOS OF UKRAINE’S FOREIGN POLICY: AN ANALYTICAL AND FORECASTING APPROACH - Girman, Alla (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2025)
The article focuses on a comprehensive analysis and forecast of Ukraine’s foreign policy amid the profound transformations of the international system in the early 21st century. It explores the main trends, influencing factors, and perspectives of Ukraine’s external course within the context of European integration, security challenges, and regional cooperation. The study is based on an interdisciplinary approach that combines political science, international relations, security analysis, and strategic forecasting. The methodological framework encompasses three key components: comparative analysis of the foreign policies of Ukraine, Poland, Lithuania, and Romania; scenario modeling of Ukraine’s foreign policy development for the medium term (2025-2030); and content analysis of expert opinions from leading specialists in international relations and diplomacy. The comparative analysis demonstrates that despite differences in political traditions, the four states share common objectives–strengthening regional security, achieving energy independence, and preserving transatlantic unity. Ukraine is gradually shifting from a reactive and defensive model toward a proactive and reform-oriented strategy aimed at integration with the EU and NATO, as well as developing subregional leadership in Eastern Europe. The key factors affecting Ukraine’s foreign policy are identified as security, energy, economic, and institutional determinants. European integration is defined as the country’s central strategic direction shaping both its domestic reforms and external behavior. Through scenario modeling, the study proposes three possible trajectories of development—reformist, conservative, and crisis-based. The reformist scenario envisions accelerated integration with the EU and NATO, enhanced defense capacity, and growing international investment. The conservative scenario implies maintaining pragmatic stability without major breakthroughs, while the crisis scenario anticipates deteriorating security and reduced international support. Expert evaluations indicate that the reformist model is the most realistic and favorable under conditions of political stability and sustained international engagement. The article concludes that Ukraine’s future foreign policy success depends on its ability to balance internal reforms, strengthen security resilience, and ensure active diplomacy in a complex and volatile global environment.